2007 International Conference on Field Programmable Logic and Applications 2007
DOI: 10.1109/fpl.2007.4380706
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral Synthesis Approach for Distributed Memory FPGA Architectures

Abstract: This paper presents an approach for efficiently mapping loops and array intensive applications onto FPGA architectures with distributed RAMs, multipliers and logic. We perform a data dependency based, two level partitioning of the application's iteration space under target FPGA architectural constraints, to achieve better performance. It is shown that, this approach can result in a super-linear speedup; linear speedup due to concurrent computation on multiple compute elements and additional speedup due to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Many studies have demonstrated that modern FPGA devices can implement an integrated controller and datapath architecture that either communicate with a monolithic memory or a banked or hierarchical memory organization [3], [4]. However, as modern FPGA devices become increasingly larger in size, the cost of global communication on-chip, both in delay and energy consumption, grows rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that modern FPGA devices can implement an integrated controller and datapath architecture that either communicate with a monolithic memory or a banked or hierarchical memory organization [3], [4]. However, as modern FPGA devices become increasingly larger in size, the cost of global communication on-chip, both in delay and energy consumption, grows rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…FPGAs have a large amount of memory distributed throughout the device. This memory neatly lends itself for tasks where distributed memory, close to the point of use, such as loop operations and array intensive operations [31]. By extension, we can use the embedded memory blocks to create the sets of registers used to set up and control the FPGA.…”
Section: Introductionmentioning
confidence: 99%